2018
DOI: 10.1038/s41598-018-35039-6
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a topologically protected state in a magnetic domain wall stabilized by a ferromagnetic chemical barrier

Abstract: The precise control and stabilization of magnetic domain walls is key for the development of the next generation magnetic nano-devices. Among the multitude of magnetic configurations of a magnetic domain wall, topologically protected states are of particular interest due to their intrinsic stability. In this work, using XMCD-PEEM, we have observed a topologically protected magnetic domain wall in a ferromagnetic cylindrical nanowire. Its structure is stabilized by periodic sharp alterations of the chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…The possibility of vortex state is disregarded as it should give rise to inhomogeneous magnetization. The magnetic curling state has been reported by Ruiz-Gómez et al 32 and is described by a magnetization at the core of the NW pointing in the direction of the nanowire axis, surrounded by a helical magnetic configuration. As previously stated, we observe a change in measured induction between regions C1 and C4 ( Figure 1e) that could arise from a difference in size of the core of such a vortex state as discussed by Bran et al and Ivanov et al 31,33 or from a change in rotation angle of the curling with respect to the nanowire axis.…”
Section: Resultsmentioning
confidence: 78%
“…The possibility of vortex state is disregarded as it should give rise to inhomogeneous magnetization. The magnetic curling state has been reported by Ruiz-Gómez et al 32 and is described by a magnetization at the core of the NW pointing in the direction of the nanowire axis, surrounded by a helical magnetic configuration. As previously stated, we observe a change in measured induction between regions C1 and C4 ( Figure 1e) that could arise from a difference in size of the core of such a vortex state as discussed by Bran et al and Ivanov et al 31,33 or from a change in rotation angle of the curling with respect to the nanowire axis.…”
Section: Resultsmentioning
confidence: 78%
“…The overarching questions regarding magnetic sensing with ferromagnetic liquids is the detection of physical changes that is conveniently done by magneto-resistance measurements in exchange-coupled metallic materials. For these applications, electro-chemical plating using a porous alumina template and strain-engineering rolled-up nanotech facilitating intrinsic strain gradients have been employed [60,61] and refined to synthesize nano-rods, nano-tubes and multi-segmented specimens [64][65][66][67][68][69][70] with variable diameter (<50 nm), and microtubules with tailored magnetization configuration [71,72] that achieve unprecedented sensitivity based on the giant magneto-impedance effect [73].…”
Section: Technological Perspectivementioning
confidence: 99%
“…This control of magnetization processes by changing the composition is particularly interesting since it has been recently shown that changes in composition can lead to full control of magnetization processes in NWs . Even more, the introduction of local changes in the composition in NWs, in which magnetization processes are fully controlled by magnetostatic interactions, can introduce topologically protected magnetic structures, very interesting from both the theoretical and application point of view …”
mentioning
confidence: 99%
“…In this sense, nanowires (NWs) are an excellent playground to understand the material properties since these have a defined magnetization easy axis along the wire axis, determined by magnetostatic (also shape) anisotropy. Recent works have shown exciting magnetic properties of NWs by controlling the magnetostatic effects: different protected states in the domain wall configuration, control in the magnetization processes, magnetic ratchet effects, etc. In fact, NWs have been proposed as building blocks of future magnetic logic devices and 3D storage devices such as race‐track memories …”
mentioning
confidence: 99%